Cardiovascular Safety of Antifracture Medications in Patients With Osteoporosis: A Narrative Review of Evidence From Randomized Studies - Alexander J Rodríguez; Bo Abrahamsen (JBMR Plus, 2021)
ABSTRACT Osteoporosis and cardiovascular (CV) disease share common risk factors and pathophysiology. Low bone mineral density (BMD) and fractures appear to increase the risk for multiple CV diseases. Equally, prevalent CV disease appears to predispose to bone loss and increase fracture rates. This relationship has naturally provoked the hypothesis that stopping bone loss may result in some CV benefit. Secondary analyses of safety and adverse event data from many randomized controlled trials (RCTs) have attempted to clarify this putative association. Recently, the discontinuation of odanacatib (anti‐cathepsin K monoclonal antibody) over stroke concerns and the imbalance in ischemic events in romosozumab‐treated (anti‐sclerostin monoclonal antibody) women compared to bisphosphonate‐treated women, has provided further justification to better characterize potential CV benefits and harms of osteoporosis medications. This review delves into the seminal, and other major RCTs of osteoporosis medications and, using both published data and additional information provided on trial registration pages, examines the evidence for CV safety and harms of these medications. Accepted and emerging “off‐target” effects are explored for validity, biological plausibility, and clinical importance. A brief research agenda is provided to stimulate the next wave of clinical development and CV understanding of osteoporosis medications. © 2021 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research.